Livestock‐type effects on biomass and nitrogen partitioning in temperate pastures with different functional‐group abundance. (25th September 2012) - Rose, L.; Hertel, D.; Leuschner, C.
Abstract: Livestock grazing can be a means to maintain biodiversity in grasslands, but the outcome for vegetation structure and species composition depends on livestock type and grazing regime. This study aims at disentangling the effects of plant functional‐group abundance and livestock type on the above‐ and below‐ground biomass and N allocation in temperate pastures. We investigated the effects of cattle, sheep and mixed stocking on above‐ground biomass (AGB) and belowground biomass (BGB) and plant N pools in a replicated grazing experiment in two pasture community types with different plant functional‐group abundance (diverse vs. grass‐dominated swards). In the six treatments, AGB was reduced up to 80% compared with an ungrazed control. Cattle reduced AGB to a larger extent than sheep in diverse pastures (80 vs 44% reduction) while sheep grazing tended to do so in grass‐dominated pastures (57 vs 46% reduction); mixed stocking led to intermediate values. Grazing reduced AGB more than the N pool in AGB, thus lowering the biomass C/N ratio relative to the ungrazed control. Neither BGB nor the N pool in BGB differed between the grazing treatments and the control plots. We conclude that livestock type and functional‐group abundance are interacting factors that influence plant biomass and N pools in swards of managed temperate pastures. The contrasting biomass removal rates of cattle and sheep could be used to increase the structural heterogeneity and total plant species pool of pastures by keeping different livestock species in neighbouring patches.